From alternating to selective distributions in chromium-catalysed ethylene oligomerisation with asymmetric BIMA ligands - Nobbs,JD; Tomov,AK; Young,CT; White,AJP; Britovsek,GJP (Catalysis Science and Technology, 2018)
The oligomerisation of ethylene with chromium-based catalysts containing asymmetric BIMA (bis(benzimidazole)methylamine) ligands produces linear alpha olefins (LAOs) that follow an alternating distribution. The catalytic activity and the degree of alternation is affected by the different ligands; in particular variations at the backbone of the ligand affect the nature of the distribution. For certain catalysts a deviation from regular alternating behaviour is observed, whereby increased amounts of 1-hexene and 1-octene (up to 29 mol%) are obtained compared to the amount expected from the distribution analysis based on C–C LAOs. This behaviour towards more selective oligomerisation to 1-hexene and 1-octene can be explained by varying probabilities of single and double ethylene insertion. The deviations will depend on the size of the metallacycle and are most pronounced early on during the metallacycle growth.